Forms of address and language ideologies: The case of a southwestern Nigerian university - Unuabonah, Foluke O. (Linguistik Online, 2018)
This paper examines the forms and functions of address terms employed among staff members and the language ideologies that inform the use of these address forms in a southwestern Nigerian university. The study is guided by Anchimbe’s (2011a) categorisation of address forms, and theories on language ideologies. The data are collected through participant-observation, oral and written interviews, and these are analysed qualitatively. The analysis reveals that forms of address used in the university include academic titles, official titles, kinship terms, social titles, nicknames, first names, surnames, and different combinations of these address forms. The address terms are derived from English, Yoruba, Nigerian Pidgin and other indigenous Nigerian languages. The address forms are informed by postmodernist and functionalist language ideologies which are influenced by cultural ideologies where interactants’ cultures play significant roles in the choice of address terms.